2014
DOI: 10.1371/journal.pone.0115179
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Strategies of Soccer Players Executing a Power vs. Placement Penalty Kick

Abstract: IntroductionWhen taking a soccer penalty kick, there are two distinct kicking techniques that can be adopted; a ‘power’ penalty or a ‘placement’ penalty. The current study investigated how the type of penalty kick being taken affected the kicker’s visual search strategy and where the ball hit the goal (end ball location).MethodWearing a portable eye tracker, 12 university footballers executed 2 power and placement penalty kicks, indoors, both with and without the presence of a goalkeeper. Video cameras were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
1
22
1
2
Order By: Relevance
“…Previous research examining the OPTIMAL theory also showed that an external focus of attention contributes to goal-action coupling by shifting concentration towards the task goal while at the same time reducing self-focus [27]. Furthermore, it has been observed when players performed an accurate penalty kick, they fixed their attention on the desired target [28] or edge of the goal [29]. In addition to utilizing an external focus, it appears that fixating on such cues provides visual information about target location that is essential to control the action.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research examining the OPTIMAL theory also showed that an external focus of attention contributes to goal-action coupling by shifting concentration towards the task goal while at the same time reducing self-focus [27]. Furthermore, it has been observed when players performed an accurate penalty kick, they fixed their attention on the desired target [28] or edge of the goal [29]. In addition to utilizing an external focus, it appears that fixating on such cues provides visual information about target location that is essential to control the action.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, attempts have been made to better understand and explain their outcomes scientifically [10][11][12][13][14][15][16]. It appears that many variables including kicking technique, visual search strategies, tactical skills and fitness contribute to the performance of penalty takers, alongside basic "chance" [17,18]. However, psychological factors are reportedly the most influential determinant of penalty outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos procuraram identificar quais são as variáveis que determinam os chutes corretos e verificaram que os chutes mais precisos são aqueles com menor velocidade (Timmis, Turner & Van Paridon, 2014), os que ocorrem independentemente da possível reação do goleiro (Castillo, Oña, Raya, Bilbao & Serra, 2010) e aqueles apresentados por jogadores que não tentaram enganar o goleiro no instante da cobrança (Smeeton & Wiliams, 2012).…”
Section: Palabras Clave: Refuerzo Condicionado; Tiro En La Portería; unclassified